2013
DOI: 10.1021/es401326a
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Hemp Cultivation and Use of Hemp-Based Thermal Insulator Materials in Buildings

Abstract: The aim of this research is to assess the sustainability of a natural fiber, such as hemp (Cannabis sativa), and its use as thermal insulator for building applications. The sustainability of hemp was quantified by life cycle assessment (LCA) and particular attention was given to the amount of CO2eq of the whole process, and the indicator greenhouse gas protocol (GGP) was selected to quantify CO2eq emissions. In this study also CO2 uptake of hemp was considered. Two different allocation procedures (i.e., mass a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 38 publications
5
84
0
Order By: Relevance
“…A considerable number of authors have worked on the assessment of both energy and environmental performances of these products. For instance, Zampori et al [75] performed an LCA of the production (technical fibre and woody core) and use of hemp for the evaluation of the impact generated by the manufacturing of a hemp mat with a thermal conductivity of 0.044 W/m K. The study included assessment of the inventory flows and environmental burdens associated with the cultivation of 1 ha of land and of the sustainability of two walls, where the insulating performances were guaranteed alternatively by hempbased or rock-wool insulating panels. The authors used mass allocation considering that, as also clarified in the previous sections, hemp cultivation delivers the following three co-products: woody core; fibre; and, dust.…”
Section: Thermo-acoustic Insulating Matsmentioning
confidence: 99%
“…A considerable number of authors have worked on the assessment of both energy and environmental performances of these products. For instance, Zampori et al [75] performed an LCA of the production (technical fibre and woody core) and use of hemp for the evaluation of the impact generated by the manufacturing of a hemp mat with a thermal conductivity of 0.044 W/m K. The study included assessment of the inventory flows and environmental burdens associated with the cultivation of 1 ha of land and of the sustainability of two walls, where the insulating performances were guaranteed alternatively by hempbased or rock-wool insulating panels. The authors used mass allocation considering that, as also clarified in the previous sections, hemp cultivation delivers the following three co-products: woody core; fibre; and, dust.…”
Section: Thermo-acoustic Insulating Matsmentioning
confidence: 99%
“…For all materials but hemp fibres, Ecoinvent Database (Ecoinvent 2010) was used as a source of foreground and background data related to both production and assembly processes as well as to the transport, electricity and fuel consumption. Instead, for the hemp processes the underlying data was derived from Zampori et al (2013).…”
Section: Results Of Multiple Criteria Assessment Of Insulating Materimentioning
confidence: 99%
“…Stefania Manzi1 et al [6] studied panels, obtained by bonding hemp hurds with different binders, characterized by a reduced environmental impact, exhibited very promising properties, both in the case of the low density panels, intended as composites for building thermal insulation, and high density panels, designed as possible substitutes for formaldehyde-bonded wood particle panels. Balciunas et al [7] and Zampori et al [8] found that in hemp-based composites for the building industry, hemp hurds are generally bonded with Portland cement, slaked lime or organic polymers. Julia Cigasova et al [9] dealt with the use of hemp hurds as organic filler in building material.…”
Section: IImentioning
confidence: 99%